Equações algébricas:aspectos históricos e um estudo sobre métodos algébricos, geométricos e computacionais de solução - Ferreira, Guttenberg Sergistótanes Santos (2014)
This study proposes a discussion of Algebraic Equations, aiming to conduct a study on the statements of the formulas, addressing the historic aspects to the various methods of problem solving, in this case, the methods were worked Algebraic, Geometric and Computational. This research was based on a literature study of the difficulties of performing demonstrations of formulas worked in the contents of mathematics as well as in the statements themselves, together with many worked examples. The analysis of the bibliographic material allowed to distribute this study by the method Algebraic problem-solving, in which they discussed the demonstration and application of resolving formulas of polynomial equations of 1st, 2nd, 3rd and 4th grades,and even citing the impossibility of the existence of formulas equations above 4 degree. In the study of the geometric method, we noticed how this geometry efficiently present in solving problems and those solutions are possible only by ruler and compass, this topic was discussed methods for solving equations of 1st and 2nd grade. About Computational Method, the study on the iterative resolution methods that are processes of successive approximations for the calculation of zeros of the function, this item was discussed methods of Newton, bisection, secant, and ropes fixed point was emphasized in so that at the end of the topic the methods under warranty and agility aspects of convergence and computational effort were compared. The achieved results show the importance of the topic of problem solving with emphasis on the statements of the formulas, and the historical context can help to demystify the process of creating and humanization of mathematics.